Efektivitas Penggunaan Media Pembelajaran Quizizz Mode Kertas untuk Meningkatkan Hasil Belajar dan Berpikir Kritis Peserta Didik Kelas VII Pada Materi Kalor di SMPN 31 Banjarmasin - Norema Ariani; Ratna Yulinda; Yasmine Khairunnisa (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
The objective of this investigation is to examine the extent to which the use of the paper-based Quizizz platform impacts the learning process in improving students’ academic achievement and critical thinking skills. This research employed a pre-experimental approach utilizing a one-group pretest-posttest design. The sample was randomly selected from one of the seventh-grade classes. Data were collected through pretest and posttest instruments to assess learning outcomes, along with a critical thinking test. The analysis revealed an average N-Gain score of 0.82, which falls into the high category. Statistical testing using the Paired Sample T-Test yielded a significance value of 0.00, indicating a statistically significant improvement in learning outcomes. A separate One Sample T-Test also revealed a significance level of 0.00 for critical thinking, confirming a significant enhancement in students’ critical thinking abilities. Further analysis of each test item demonstrated that all questions were effective in measuring various aspects of critical thinking, including interpretation, analysis, evaluation, and drawing conclusions. These findings suggest that implementing paper-based Quizizz as a learning tool can effectively foster comprehensive critical thinking and deepen students’ understanding of the subject matter.